2001
DOI: 10.1038/sj.sc.3101156
|View full text |Cite
|
Sign up to set email alerts
|

Does a colostomy alter quality of life in patients with spinal cord injury? A controlled study

Abstract: Study Design: Prospective controlled comparative analysis. Objective: To determine whether a colostomy changes quality of life in patients with a spinal cord injury. Method: A previously validated questionnaire designed to assess quality of life in spinal injured patients (Burwood Questionnaire) was sent to 26 spinal cord injured patients with colostomies and 26 spinal cord injured patients without colostomy. The two groups were matched for level of injury, completeness of injury, length of time since injury, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 8 publications
1
48
0
Order By: Relevance
“…Nine studies (aggregate N ¼ 590) examined the effect of colostomy after SCI (Table 11). [60][61][62][63][64][65][66][67][68] Given the ethical nature of this treatment (that is few safe options once they reach the point of [60][61][62][63][64] and Level 5 evidence (from one study) 68 that colostomy reduces the number of hours spent on bowel care. There is Level 4 evidence (from one retrospective pre-post study) 60 that colostomy greatly simplifies bowel care routines.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies (aggregate N ¼ 590) examined the effect of colostomy after SCI (Table 11). [60][61][62][63][64][65][66][67][68] Given the ethical nature of this treatment (that is few safe options once they reach the point of [60][61][62][63][64] and Level 5 evidence (from one study) 68 that colostomy reduces the number of hours spent on bowel care. There is Level 4 evidence (from one retrospective pre-post study) 60 that colostomy greatly simplifies bowel care routines.…”
Section: Resultsmentioning
confidence: 99%
“…Previous publications describe the formation of an intestinal stoma in SCI patients for management problems, including chronic gastrointestinal symptoms, 10 decubitus ulcers, 9 anal cancer, 10 rectal cancer, Stoma formation in SCI patients G Branagan et al trauma, 11 bowel obstruction, 11 and rectovesical fistula.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The failure of conservative measures to treat these chronic problems in some patients has led to the use of elective surgical treatments such as anterior sacral root stimulation, 4,5 antegrade colonic lavage [6][7][8] and stoma formation. 9,10 The effect of colostomy formation on both quality of life 11 and time taken for bowel care 9,10 is well recorded, including data from our own group.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are partly in accordance to several previous studies, which have shown that colostomy improves QoL in individuals with SCI. 26,27,30,31,35 In contrast Randall et al 36 showed that QoL was not significantly different between spinal cord injured with or without colostomy. This is supported by Luther et al 37 who showed no significant difference in persons with SCI with or without colostomy concerning QoL but large numbers of respondents in both groups reported being very unsatisfied with their bowel care program.…”
Section: Discussionmentioning
confidence: 86%